2011
DOI: 10.1007/s00436-011-2467-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungus mediated silver and gold nanoparticles against Aedes aegypti larvae

Abstract: Chrysosporium tropicum is a pathogenic fungus. It is known to be an effective mosquito control agent. In the present study, we have synthesized the silver and gold nanoparticles using C. tropicum. These nanoparticles have been characterized through Microscan reader, X-ray diffractometer, transmission electron microscopy, and further confirmed by scanning electron microscopy. The characterization study confirmed the spherical shape and size (2-15 and 20-50 nm) of gold and silver nanoparticles. These silver and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(46 citation statements)
references
References 22 publications
2
43
1
Order By: Relevance
“…B. thuringiens was often known for its mosquito larvicide effects whereas the resistance against cry toxins neglected their usage in the recent decades (Surendran and Vennison 2011;Cadavid-Restrepo et al 2012;Chenniappan and Ayyadurai 2012). The present study exemplified that the formation of yellowish brown color was due to reduction of silver ions that indicated the formation of silver nanoparticles and exhibit yellowish brown color in aqueous solution due to excitation of surface plasmon vibrations in silver nanoparticles which correlated with the results obtained by Mukherjee et al (2001), Vigneshwaran et al (2007), Soni and Prakash (2012), and Najitha .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…B. thuringiens was often known for its mosquito larvicide effects whereas the resistance against cry toxins neglected their usage in the recent decades (Surendran and Vennison 2011;Cadavid-Restrepo et al 2012;Chenniappan and Ayyadurai 2012). The present study exemplified that the formation of yellowish brown color was due to reduction of silver ions that indicated the formation of silver nanoparticles and exhibit yellowish brown color in aqueous solution due to excitation of surface plasmon vibrations in silver nanoparticles which correlated with the results obtained by Mukherjee et al (2001), Vigneshwaran et al (2007), Soni and Prakash (2012), and Najitha .…”
Section: Discussionsupporting
confidence: 93%
“…Of which, B. thuringiensis var. israelensis and B. sphaericus are effective but serious resistance as high as 50,000-fold has evolved where B. sphaericus is used against Culex mosquitoes (Soni and Prakash 2011). Recently, the laboratory resistance in the mosquitoes has been demonstrated to some isolates of B. thuringiensis (Surendran and Vennison 2011;CadavidRestrepo et al 2012;Chenniappan and Ayyadurai 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Soni and Prakash [11] have reported the fabrication of AgNPs by using a popular fungus C. tropicum, calculate LC50 and LC90 values as 4 and 8.91 against Dengue vector, these values were comparatively much higher than the LC50 and LC90 values measured in the current research work. Priyadarshini et al [12] have reported that Euphorbia hirta mediated AgNPs exhibit LC50 as (10.14 ppm, 27.89 ppm) and LC90 as (31.98 ppm, 69.84 ppm).…”
Section: Resultscontrasting
confidence: 47%
“…These kinds of nanoparticles have exhibited efficacy against mosquito larvae (e.g., Aedes, Culex and Anopheles). [60][61][62][63][64][65] In addition, leaf extracts from plants have been used for silver nanoparticle production and have become an eco-friendly alternative for adulticidal activity against filarial, dengue and malaria vector mosquitoes (Table 2). [66][67][68][69] An interesting review on biogenic silver nanoparticles against mosquitoes was recently reported.…”
Section: Nanoinsecticide Against Mosquitoesmentioning
confidence: 99%